A Multi-Objective Constrained Optimization Model for Designing a Green Closed Loop Supply Chain Network in Tax System - Sergeevna, SergushinaElena; Valentinovn, KarageziyanMarina; Ivanovna, YatsunovaTatiana; Talyatovna, RustamovaIrada; Nikolaevich, ZhadanVladimir; Vladimirovich, Kabanov Oleg; Anatolievich, GrigoryevAndrey; Lesovik, RuslanV; Khyzhak, NatalyaP; Albertovna, ShereuzhevaMadina; Mikhailovich, UshakovRuslan; Yurevna, KamchatovaEkaterina; et al. (Industrial Engineering & Management Systems, 2021)
The multi-objective constrained model proposed for closed green supply chain in the enterprise development. Small and medium businesses make a significant contribution to the economic life of any country and to the maintenance of employment and economic growth. This paper focuses on the pricing problem of a two-stage closed-loop supply chain (CLSC) considering the cross-channel recycling and channel preference based on a single manufacturer and a single traditional retailer in the digital environment. The article analyzes the indicators of taxation of small and medium-sized businesses in the Republic of Mordovia and draws conclusions about the advantages of using a digitalization system for small and medium-sized businesses. Manufacturer’s pricing decreases when channel preferences are constant and cross-channel recovery rates increase. Retailer’s pricing remains stable as the cross-channel recovery rate has less affected on it. This information will be a helpful guideline for the manager to select suitable pricing strategies based on the company scenario. KCI Citation Count: 0